CONSERVATION CHILD’S ATTACHMENT TO BOTH PARENTS IN THE DIVORCE: ON THE PROBLEM RESEARCH - Sklyarova, Tatyana; Kupriianova, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
his paper discusses the development of a child whose parents are divorced. In deciding with whom the child should stay, the court is based on his interests, it is very often decisive is the child's own opinion about who he wants to live. An important problem in this situation is the active influence of one parent (most of whom currently live child) on the decision-making process a child. To achieve the desired result the parent often resorted to negative methods of influence on your child, creating a negative image of the second parent. To minimize the negative effects of divorce of parents for the child's development the positive attitude of the child to both parents after a divorce is needed. However, judicial practice shows that maintaining a positive attitude of the child to both parents after a divorce, are often deliberately destroyed by adults for their own benefit. The objects of the analysis were 30 court cases from attorney's Kupriyanova court practice.The subject of analysis is the position of the parent with whom the child resides at the time of the court with respect to the second parent. For the processing of the experimental data used statistical package SPSS. It was obtained that the probability of the formation of the parent with whom the child remains after the court decision, the child's negative attitude towards the other parent more than 1/3.